New hybrids of maize (Zea mays L.) in the lowlands and dry tropical regions of Mexico, recovered by gametic selection. - Vega, Cristina; Burciaga, Gustavo; Arreola, Jesús; Navarro, Enrique; Gutiérrez, José L. (Agronomía Mesoamericana, 2016)
The aim of this study was to improve the agronomic quality of the tropical lines AN1 and AN2 which have good combining ability; besides their germoplasm is part of a large number of commercial hybrids generated by the Instituto Mexicano del Maíz “Dr. Mario E. Castro Gil”. Eto Blancoand Blanco Dentado 2 were used as a source of gametes and crossed with AN1 and AN2, respectively. This study included recovered lines with different level of inbreeding, five dwarf single crosses and the original lines AN1 and AN2 which were used as testers. A randomized complete block design was used with two replications in each of the three locations during 1989-1990. The objectives were: 1. to select recovered lines on the bases of their combining ability and agronomic traits to generate new hybrids. 2. To determine the effectiveness of the diverse testers. The results showed that gamete selection was efficient in improving AN1 and AN2 lines for most of the traits evaluated such as grain yield, percent of fussarium on ears, except for percent of husk coverage. That recovered lines of AN1 were superior to those of AN2 lines for grain yield. A total of fifteen lines of AN1 and 7 lines of AN2 were identified using gamete selection.